Role of Personality Traits, Self-Efficacy and Procrastination on Cyberloafing Behavior: A Moderated Mediation Study - S., Sakthi; Ravi, D.; Bansal, Dolly; Madiha, Maria; Bharaty, Sneha; Satija, Devika; Mohan, Devika; M, Selvapriya; Chakraborty, Shatarupa (Defence Life Science Journal, 2025)
The internet has revolutionised the way work is carried out and has contributed significantly to the enhancement of organisations, employees and students. With time, internet usage in organisations and institutes has taken a new turn. One such concern of internet usage is cyberloafing. Cyberloafing has caused an obvious drop in employee and student productivity, and subsequently cost organisation much time and money. Studies have tried to identify factors that influence cyberloafing behaviours; however, have led to few inconclusive arguments. With a total sample size of 315 (females=181 and males=134), the present study aims to understand how self-efficacy mediates and procrastination moderates the relationship between personality traits and cyberloafing behavior. Using a survey research design, the data was collected through online and paper-pencil modes. Pearson’s product moment correlations and stepwise regression revealed that personality traits have connection with cyberloafing behavior. Moreover, moderated-mediation analysis showed that self-efficacy does not act as a mediator for personality traits (conscientiousness and extraversion) and cyberloafing. Similarly, procrastination too does not moderate the relation between the two variables. The present study sheds light on existence of cyberloafing at workplace and academics, and emphasises on the importance of understanding the factors influencing cyberloafing